The Comparison of Food Dehydrator and Intermittent Microwave Drying (IMD) on the Quality Characteristics of Butterfly Pea Flower (Clitoria ternatea L.) - Asri Widyasanti; Kaylasari Rhamadani; Syifa Khairunnisa; Vannesa Beatrix (Journal of Food and Agricultural Product, 2026)
Butterfly pea flower (Clitoria ternatea L.) has high moisture content and heat sensitive anthocyanin pigments, which makes drying method selection critical to maintain product quality. Conventional drying often requires long processing time, while rapid drying may cause quality degradation. This study aimed to compare the effectiveness of food dehydrator and intermittent microwave drying on the moisture content and color characteristics of dried butterfly pea flower. Drying using a food dehydrator was carried out at 65°C for 6 hours, while intermittent microwave drying was performed at 400 W with a heating cycle of 60 seconds on and 60 seconds off for a total of 24 minutes. Moisture content was analyzed using the thermogravimetric method, and color characteristics were measured using a chromameter based on CIE L*, a*, and b* parameters. The results showed that intermittent microwave drying significantly reduced drying time compared to the food dehydrator. The final moisture content obtained using intermittent microwave drying was lower than that of the food dehydrator and met the standard for dried herbal products. Both drying methods caused changes in color, with food dehydrator producing more uniform color, while intermittent microwave drying showed a greater shift toward yellow red tones. These results indicate that intermittent microwave drying is more efficient in moisture removal, while food dehydrator provides better color uniformity. Selection of the drying method should consider the balance between processing efficiency and color quality. Keywords: butterfly pea flower, drying method, moisture content, color characteristics, intermittent microwave drying